Axes of alpine jade in Denmark: the point of view of an alpine prehistorian - Pierre Pétrequin (Danish Journal of Archaeology, 2012)
This article presents the typological and chronological relationship between information derived from the central find locations for alpine jade axes around the area of Mount Viso, and the examples found elsewhere in Europe. Furthermore, by making comparisons between the composition of the hoards of alpine axes found in northwestern Europe to those located in southern Scandinavian, it is argued that the Scandinavian examples presumably reached the area via secondary centres of distribution.